Drivers and Effects of Internationalising Innovation by SMEs - Christian Rammer; Anja Schmiele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper investigates the drivers and effects of the internationalisation of innovation activities in SMEs based on a large data set of German firms covering the period 2002-2007. We look at different stages of the innovation process (R&D, design, production and sales of new products, and implementation of new processes) and explore the role of internal resources, home market competition and innovationrelated location advantages for an SME's decision to engage in innovation activities abroad. By linking international innovation activities to firm growth in the home market we try to identify likely internationalisation effects at the firm level. The results show that export experience and experience in knowledge protection are highly important for international innovation activities of SMEs. Fierce home market competition turns out to be rather an obstacle than a driver. High innovation costs stimulate internationalisation of non-R&D innovation activities, and shortage of qualified labour expels production of new products. R&D activities abroad and exports of new products spur firm growth in the home market while there are no negative effects on home market growth from shifting production of new products abroad.
Older version: http://hdl.handle.net/10419/24730
Keywords: O32; O31; L25; L22; F23; O47; 330; Internationalisation of Innovation; Globalisation; SMEs; Effects of Innovation; Absorptive Capacities; Market Structure; Innovation; Klein- und Mittelunternehmen; Industrielle Forschung; Auslandsniederlassung; Globalisierung; Export; Immaterialgüterrechte; Deutschland